Моделювання технічного стану суднових конструкцій з використанням ANSYS Structural - Анцифєров, Ігор (Видавництво Львівської політехніки, 2016)
Determination of technical condition is carried out during surveys made by ship surveyors of the classification society. Prediction of the technical condition of the vessel's hull as a complete complex multi-system has good prospects. Using ANSYS Structural program complex for assessment of physical deterioration of the hull allow to optimize the performance of planned repairs. Usually vessel repair planning allows to optimize the operatinal costs.
Keywords: ANSYS Structural; технічний стан; корпусні конструкції; корозійний знос; кінцеві елементи